Cardiac Troponins and Their Prognostic Importance in Patients with Suspected Acute Coronary Syndrome and Renal Dysfunction. (6th January 2020) - Eggers, Kai M; Lindahl, Bertil; Carrero, Juan J; Evans, Marie; Szummer, Karolina; Jernberg, Tomas
Abstract: BACKGROUND: Cardiac troponin (cTn) is important for risk assessment in patients with suspected acute coronary syndrome (ACS). cTn concentrations may, however, be affected by renal dysfunction, and the clinical importance of this interrelation is not well established. We investigated the association between cTnT and cTnI (measured with conventional assays and a more sensitive assay) with the estimated glomerular filtration rate (eGFR) and also assessed the ability of cTn to predict the 1-year all-cause mortality. METHODS: This retrospective registry-based study used data from 309454 admissions to Swedish coronary care units. cTn associations with eGFR and mortality were assessed using different regression models and by calculating multivariable-adjusted c -statistics. RESULTS: cTnT concentrations exhibited stronger associations with eGFR than cTnI concentrations (conventional cTnT assay: β = −0.113; more sensitive cTnT assay: β= −0.186; pooled conventional cTnI assays: β = −0.098). Overall, cTnT provided greater prognostic accuracy than cTnI. This was most evident in non-ACS patients with normal or mildly reduced eGFR when using the more sensitive assay. Despite higher mortality rates, no consistent increases in the c -statistics of cTn were seen with severely reduced eGFR irrespective of the presence of ACS or non-ACS. CONCLUSIONS: cTnT concentrations exhibited stronger associations with reduced eGFR than cTnI concentrations in patients admitted because of suspected ACS. cTnT, particularly when measured using the more sensitive assay, also tended to be a stronger prognosticator. However, the relative significance of the obtained results must be considered in the context of the severity of renal dysfunction and whether ACS is present.